EFFECTS OF INTERVENTIONAL SPORTS ACTIVITIES ON THE PERFORMANCE IN PHYSICAL EDUCATION OF HEARING IMPAIRED STUDENTS SCHOOL YEAR 2016-2017 - Francis R. Gura, MAT; Tianio, Jomar S.; Jefferson De Castro, MAT; Charlie D. Sabinay, MAT (International Journal of Multidisciplinary Research and Studies, 2023)
The main aim of the study was to determine the acceptability and effectiveness of instructional videos in Teaching Arnis to Grade Seven (7) students of Casimiro A. Ynares Sr. Memorial National High School (CAYSMNHS) for the school year 2016 – 2017. The researcher used a self-made test and scoring rubric to determine the performance of Grade 7 respondents in the Arnis Game. The population for the study consisted of 20 hearing-impaired students directly handled by the researcher. The respondents were chosen via random sampling using the lottery method. The developed instructional videos in teaching arnis to Grade Seven (7) students used a given copy of the Instructional Videos Presentation in Arnis game as a guide in their instructional materials for the third grading period of their subject. The 20 Grade 7 hearing-impaired students who were enrolled in MAPEH 7 used the Traditional Method of teaching, they were rated based on the teachers made test and criteria of scoring rubrics; A researcher constructed practicum test in MAPEH 7 to determine the performance of the respondents considered the objectives of the topics in arnis such as basic striking techniques in terms of application skill, strategy, rules, and convention. This study focused on the acceptability of the developed instructional video through evaluation of experts in Arnis game validating the instructional videos. The chosen experts were certified MAPEH and Special Education Teachers and have full knowledge of it. The developed instructional video lasted for 15 minutes and should be divided into various sequences to emphasize the skills such as basic stance and striking techniques in step-by-step sequences. The language to be used is English and was recorded in mp4 format. After doing the scripts and arranging the shoot list by location the developed instructional video was conducted at the Casimiro A. Ynares Sr. Memorial National High School (CAYSMNHS) campus, with the assistance of MAPEH and Special Education teachers. The primary objective of the study is to determine the effectiveness of the sports activities through appropriate instructional videos to the physical skills of hearing-impaired students, which in turn will hopes to provide relevant learning while in the mainstream. It also seeks to find out how much these interventional sports activities in the video will gain impact the student’s cognitive and socio-emotional skills. A pretest before/pretest was administered to the respondents beginning of the first grading period while a posttest was done at the end of the second grading period. The 20 respondents utilized & exposed to the development of Instructional Videos in Arnis. The performances of the 20 Grade 7 hearing-impaired respondents were compared to determine the effects of the Instructional Video on the student’s performance in Arnis. After gathering and computing the data, the results of the Before/Pretest and After/post-test of the 20 respondents revealed an increase in the level of performance of the students. It is possible that the 20 respondents gained additional knowledge from the instructional video. Several students like the instructional video because it is easy to understand and there is immediate reinforcement. The data revealed that the level of performance of the respondents increased in their performance through written and practicum test. The effectiveness of instructional videos in teaching Arnis game activities was significant as manifested by the additional knowledge from them. The learners exposed to the instructional videos gained more knowledge due to the improvement and the positive result of their scores in the posttest. Based on the findings, the following conclusions were drawn: the utilization of instructional videos in arnis contributes to the improved performance of hearing-impaired students due to the provision of multisensory experiences specifically visual learning. The instructional videos are an important aid in teaching Physical Education, especially basic skills in Arnis. It accounts for acquiring knowledge and can provide good results among students regarding their performance. Using the instructional videos for the selected topic in Arnis made the performance of the respondents better. It helped the teachers in implementing and imparting knowledge to their hearing-impaired students in an easy and effective way. Students, on the other hand, could work easily with both visual and verbal representations, increasing their motivation and enhancing their learning experience.